The Influence of Work Life Balance and Burnout on Employee Job Satisfaction at PT SBCR Cirebon - Riska Ameliya; Siti Maryam (CV. AFDIFAL MAJU BERKAH, 2026)
This study explores the effects of Work Life Balance and Burnout on employee Job Satisfaction at PT SBCR Cirebon. Job satisfaction among employees is crucial for organizational performance since it relates to productivity, commitment to the organization, and retention of staff. This research employed a quantitative approach defined by an associative structure. The research comprised all employees of PT SBCR Cirebon, employing a saturated sampling method that resulted in a sample size of 100 respondents. Data collection was conducted using structured questionnaires, and data analysis employed multiple linear regression with the assistance of IBM SPSS software. The findings show that Work Life Balance positively and considerably affects Job Satisfaction, whereas Burnout negatively and significantly impacts Job Satisfaction. Additionally, Work Life Balance and Burnout together influence employee Job Satisfaction. The coefficient of determination indicates that the two independent variables account for 47.5% of the variation in Job Satisfaction, while the other 52.5% is due to factors not considered in this analysis. The findings emphasize the importance of organizational practices that encourage work-life balance and effective burnout prevention as vital approaches to enhance employee satisfaction and overall operational performance.